Cloning and enhancing lumbrokinase production from local Eisenia fetida by signal peptide engineering for effective thrombosis treatment. - Adeeba Tabassum; Nadia Zeeshan; Amber Afroz (PLoS ONE)
Thrombosis, the formation of blood clots in the circulatory system, is a major global health concern. Lumbrokinase, found in earthworms, is promising natural source of antithrombotic compounds. Traditional extraction methods from earthworms can be challenging due to contamination, making genetic engineering an attractive option. In this study lumbrokinase gene from the local earthworm species Eisenia fetida was isolated, sequenced, and cloned in the expression vector. The full-length lumbrokinase cDNA spanning 744 nucleotides was successfully amplified by PCR and the obtained sequence was submitted at GenBank under the accession # OP820958. The active side residues, 2D and 3D structure of the deduced protein sequence (248-amino acid) were determined by I-TASSER. Moreover, an innovative recombinant expression strategy (i.e., expression in pET22b (+) vector with pelB signal peptide and the pET28a (+) vector with SUMO tag) was employed to enhance lumbrokinase production and yield. Lumbrokinase amounting to approximately 6.8 mg/l in pET22 b (+) and 8.9 mg/l in pET28-SUMO was obtained from 1-liter culture. In the fibrin plate assay, specific activities of 1942 U/mg and 2027 U/mg were found from periplasmic and cytoplasmic space, respectively. In an in vitro blood clot lysis assay, recombinant lumbrokinase showed 25.67% and 66.23% clot lysis after 240-minute incubation at 37°C. This study discovered the presence of lumbrokinase genes in local earthworms and made significant contributions to the development of recombinant fibrinolytic enzymes with prospective applications in thrombotic disease treatment as an alternative to conventional approaches.